2015
DOI: 10.1371/journal.pone.0143025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of a Real-Time PCR Assay Targeting senX3-regX3 versus Other Molecular Strategies Commonly Used in the Diagnosis of Tuberculosis

Abstract: BackgroundNucleic acid amplification tests are increasingly used for the rapid diagnosis of tuberculosis. We undertook a comparative study of the efficiency and diagnostic yield of a real-time PCR senX3-regX3 based assay versus the classical IS6110 target and the new commercial methods.MethodsThis single-blind prospective comparative study included 145 consecutive samples: 76 from patients with culture-confirmed tuberculosis (86.8% pulmonary and 13.2% extrapulmonary tuberculosis: 48.7% smear-positive and 51.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… MGIT, LJ,7H11 sp,ba,bal.,ti In,ab,pf,ti 89/23 30 4 7 71 Rao 2016 [ 30 ] Cross-sectional India 100 200 44/56 16sRNA ? MGIT sp 100/0 44 2 0 54 Rozales 2014 [ 31 ] Cross-sectional Brazil 447 447 42/405 IS6110 ZN 7H9,MGIT sp,bal 124/0 41 7 1 75 Sanjuan-Jimenez 2015 [ 32 ] Case-control Spain 153 145 76/69 senX3-regX3 ZN LJ,MGIT sp,ba,bal pf,In,ur,csf,ar 125/20 65 0 11 69 Sanjuan-Jimenez 2015 [ 32 ] Case-control Spain 153 145 76/69 IS6110 ZN LJ,MGIT sp,ba,bal pf,In,ur,csf,ar 125/20 72 9 4 60 Acid-fast stain: ZN, Ziehl-Neelsen; Culture: MGIT, Mycobacteria growth indicator tube; LJ, Löwenstein-Jensen; 7H9, Middlebrook 7H9 Broth. Respiratory specimen: sp., sputum; ba, broncheal/tracheal aspirate; bal., bronchialalveolar lavage; ti, tissue specimen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… MGIT, LJ,7H11 sp,ba,bal.,ti In,ab,pf,ti 89/23 30 4 7 71 Rao 2016 [ 30 ] Cross-sectional India 100 200 44/56 16sRNA ? MGIT sp 100/0 44 2 0 54 Rozales 2014 [ 31 ] Cross-sectional Brazil 447 447 42/405 IS6110 ZN 7H9,MGIT sp,bal 124/0 41 7 1 75 Sanjuan-Jimenez 2015 [ 32 ] Case-control Spain 153 145 76/69 senX3-regX3 ZN LJ,MGIT sp,ba,bal pf,In,ur,csf,ar 125/20 65 0 11 69 Sanjuan-Jimenez 2015 [ 32 ] Case-control Spain 153 145 76/69 IS6110 ZN LJ,MGIT sp,ba,bal pf,In,ur,csf,ar 125/20 72 9 4 60 Acid-fast stain: ZN, Ziehl-Neelsen; Culture: MGIT, Mycobacteria growth indicator tube; LJ, Löwenstein-Jensen; 7H9, Middlebrook 7H9 Broth. Respiratory specimen: sp., sputum; ba, broncheal/tracheal aspirate; bal., bronchialalveolar lavage; ti, tissue specimen.…”
Section: Resultsmentioning
confidence: 99%
“…Medical resources are limited in the majority of these countries [ 1 ]. Although recent studies have revealed that RT-PCR assays have good diagnostic performance for TB, there are unignorable discrepancies between their results [ 10 , 20 32 ]. Moreover, none of the researchers could demonstrate precise diagnostic accuracy due to their limited statistical power.…”
Section: Introductionmentioning
confidence: 99%